FAKTOR RISIKO KEJIADIAN KUSTA DI WILAYAH KERJA PUSKESMAS ELLY UYO KOTA JAYAPURA - Puspitasari, Irma; Assa, Inriyanti; Adimuntja, Natalia P; Bouway, Dolfinus Y.; Pariaribo, Konstantina; Asriati, Asriati (Jurnal Kesehatan Masyarakat, 2023)
Leprosy is caused by the bacterium mycobacterium leprae, which can cause damage to the skin, nerves, eyes and can even cause disability to the sufferer. The purpose of this study was to determine the risk factors for leprosy in the working area of the Elly Uyo Health Center, Jayapura City. This type of research is analytic observational with a case control. The case group is leprosy sufferers and the control group is close neighbors of lepers who do not have leprosy. The sampling technique was simple random sampling for the case group and purposive sampling for the control group. The number of samples is 72 respondents with a ratio of 1:1. The measuring instrument used was a questionnaire. Data were analyzed using univariate and bivariate methods using the chi-square with a 95% confidence level followed by multivariate tests using logistic regression. The results of the chi-square showed that there was a risk between clothing cleanliness (p=0.047; OR=4.000) the habit of borrowing towels (p= 0.31; OR=3,250), and history of contact (p=0,000; OR=18,600) with leprosy. While there is no risk between levels of education (p= 0.107; OR=0.143), economic status (p=0.733; OR=0.625) and bathing habits (p=0.674; OR=0.471) with leprosy. The results of the multivariate analysis showed that the most dominant variable with the incidence of leprosy in the working area of the Elly Uyo Health Center was contact history (p=0.000; OR = 32.511). It is hoped that the community will not have too frequent contact with leprosy sufferers and maintain personal hygiene.Keywords: Leprosy, Elly Uyo Health Center, Risk Factors